PERAN LEMBAGA ADAT DALAM PENYELESAIAN KONFLIK SOSIAL DAN DAMPAKNYA TERHADAP KESEJAHTERAAN MASYARAKAT NEGERI WAAI KABUPATEN MALUKU TENGAH - Bakarbessy, Derek (JURNAL BADATI, 2025)
This research examines the role of traditional institutions in social conflict resolution and their impact on community welfare in Negeri WAAI, Central Maluku Regency. Using a qualitative approach with case study methods, this research involves in-depth interviews, participatory observation, and focus group discussions with various stakeholders. The results show that traditional institutions play a strategic role in conflict resolution through mechanisms based on the local wisdom of "Pela Gandong". The implemented conflict resolution system covers five main typologies: customary land conflicts, marine resources, inter-clan disputes, ritual conflicts, and generational conflicts, with an average success rate of 86.6%. Positive impacts are evident in improved economic welfare, strengthened social cohesion, cultural preservation, and sustainable environmental management. Major challenges include modernization, generational gaps, and the complexity of contemporary conflicts. This research recommends strengthening traditional institutional capacity, enhancing synergy with government, and developing regeneration programs for the sustainability of traditional systems in conflict resolution.